경도인지 장애 평가 및 분석 시스템 - 최성훈(Sung-Hoon Choi); 주문일(Moon-Il Joo); 양영애(Yeong-Ae Yang); 김희철(Hee-Cheol Kim) (한국정보통신학회논문지, 2016)
As the aging society is accelerated, the population with dementia grows significantly faster. Because there is no complete cure of dementia, it is of great importance to detect the disease at a very early stage and prevent its fast aggravation through evaluation of MCI(Mild Cognitive Impairment) which happens before dementia. The current assessment of MCI conducts only in the form of hand-written data and by 1:1 face to face communication between the subjects and the examiners. Due to this, both examiners' fatigue rate and evaluation error rate increase. Further, there are some limitations in utilizing and analyzing data collected. Against the problems, therefore, there is a need to develop a computerized system by which MCI is assessed, and the results are saved and analyzed. This paper presents the development of such a system enabling MCI evaluation, its related data collection and analysis. 최근 인구 고령화가 급속히 진행되면서 치매인구가 빠른 속도로 증가하고 있다. 치매는 완벽한 치료법이 없기 때문에 경도인지 장애 평가를 통해 조기 발견하여 예방 훈련하는 것이 중요하다. 기존의 경도인지 장애 평가는 수기형태로 이루어지며, 피검자와 검사자의 1:1 대면 평가가 원칙이다. 이는 검사자의 피로도 증가와 이로 인한 평가오류의 가능성을 증가시킨다. 또한 도출된 데이터도 수기 형태이기에 다양한 방식으로 분석 및 활용하기에는 한계가 있다. 따라서 기존 방식의 제한점을 극복 수 있는 시스템화가 가능한 어플리케이션을 활용하여 평가하고, 그 결과를 저장 및 분석할 수 있는 시스템 개발이 필요하다. 본 논문은 경도인지 장애를 평가할 수 있는 피검자와 검사자용 어플리케이션과 평가 데이터를 저장 및 분석할 수 있는 시스템을 개발하고자 한다.